Mean platelet volume (MPV) and red blood cell distribution width coefficient of variation (RDW_CV) as prognostic markers in community-acquired pneumonia in children: a cross-sectional study - Masoud Kiani; Hengameh Shahnouri; Hasan Mahmoodi; Mohammad Pournasrollah; Hemmat Gholinia Ahangar; Mohsen Mohammadi (SpringerOpen, 2024)
Abstract Background Community-acquired pneumonia (CAP) is a major global health threat for children, causing numerous hospitalizations and deaths. CAP is a leading cause of mortality in children under five and results in millions of hospital admissions each year. Identifying reliable prognostic markers is crucial. Mean platelet volume (MPV) and red blood cell distribution width coefficient of variation (RDW_CV) are accessible and cost-effective options for prognosis assessment. This study investigates MPV and RDW_CV as prognostic markers in children with CAP. Methods This cross-sectional study included 150 children aged 1-15 years diagnosed with CAP upon initial examination and admitted to the hospital. CAP diagnosis was based on clinical symptoms, physical examination, and/or radiographic findings, with hospitalization criteria set for CAP in children. CAP severity was assessed using the Clinical Respiratory Score, categorizing patients into mild, moderate, and severe groups. MPV and RDW_CV were compared among these groups. Results Among the patients, 71 (47.3%) were girls, and 79 (52.7%) were boys. The average hospitalization duration was 6.24 ± 3.82 days, with a median of 5 days. Disease severity distribution was 58 (38.7%) mild, 54 (36.0%) moderate, and 38 (25.3%) severe. Both RDW_CV and MPV were higher in severe cases and in children hospitalized for more than 10 days (P < 0.001). A significant positive correlation was observed between RDW_CV and MPV (r = 0.636, P < 0.001). Mean RDW and MPV values were significantly elevated in children needing ICU admission and those with pleural effusion (P < 0.001). The RDW_CV cutoff was 13.75, with 97.4% sensitivity and 80.4% specificity. The MPV cutoff was 8.25, with 78.9% sensitivity and 69.6% specificity. Conclusion Elevated RDW_CV and MPV levels are associated with severe CAP in hospitalized children, providing valuable prognostic insights. RDW_CV is a more precise prognostic indicator than MPV, demonstrating superior predictive value in CAP management.